Integration of STATCOM and ESS for power system stability improvement - Ibrahim Alhamrouni; Rasyid Ismail; Mohamed Salem; Bazilah Ismail; Awang Jusoh; Tole Sutikno (Institute of Advanced Engineering and Science, 2020)
The power system enters a state of voltage instability due to the inability of the power system to meet the demand for active power and reactive power due to the increase of system load. In order to stabilize the power system, the installation of STATCOM and ESS needs to be performed. The main objective of this study is to identify the suitable size and location of STATCOM and ESS for power system stability improvement. First, the IEEE 14 bus system was simulated using DIgSILENT software in ideal condition. Then, the system loadability was increased up to 200% of initial value to locate the weakest bus. This study includes the applicable location and sizing of STATCOM and ESS towards improving power system stability. The results showed that the application of STATCOM and ESS with the most reliable size can increase the bus voltage (p.u and kV) of IEEE 14 bus system thus improving the power system stability. For recommendation, the power system stability can be improved by installing multiple STATCOM and ESS at other load buses and applying a controller to both STATCOM and ESS to improve the effectiveness of generating and absorbency of active and reactive power in the power system.